Hubungan Antara Modalitas Belajar Dengan Prestasi Belajar Siswa Kelas Tinggi SDN 261 Tarasu Kecamatan Kajuara Kabupaten Bone - Idris Idris; Nurul Fausiah; Amin Amin (Universitas Negeri Makassar, 2022)
This research is a type of correlational research that aims to determine whether there is a significant relationship between learning modalities and student achievement in high grade SDN 261 Tarasu, Kajuara District, Bone Regency. Variable X in this study is student learning modality, while variable Y is student achievement. The population in this study were high-class students at SDN 261 Tarasu, Kajuara District, Bone Regency, with a total of 67 students, of which there were 20 students in class IV, 21 students in V, and 26 students in class VI. The total population is all high-class students at SDN 261 Tarasu, Kajuara District, Bone Regency. The sampling technique in this study used a non-probability technique, namely a saturated sample. Data collection through questionnaires and documentation. The data analysis technique is descriptive statistical analysis with inferential statistical analysis. Based on the results of descriptive statistical analysis, the students' learning modalities are in the good category with an average analysis of 86.77 and a percentage of 72.31%. Learning achievement is in the good category with an average analysis of 82.62 and a percentage of 68.85%. Then, based on inferential statistics, the tcount value (4.9124) is greater (>) the ttable value (1.66864) at the 5% significance level. Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between learning modalities and student achievement in high grade SDN 261 Tarasu, Kajuara District, Bone Regency, but learning modalities did not always affect student achievement. Penelitian ini adalah jenis penelitian korelasional yang bertujuan untuk mengetahui ada tidaknya hubungan yang signifikan antara modalitas belajar dengan prestasi belajar siswa kelas Tinggi SDN 261 Tarasu Kecamatan Kajuara Kabupaten Bone. Variabel X dalam penelitian ini adalah modalitas belajar siswa, sedangkan variabel Y adalah prestasi belajar siswa. Populasi dalam penelitian ini adalah siswa kelas Tinggi SDN 261 Tarasu Kecamatan Kajuara Kabupaten Bone, dengan jumlah 67 siswa, dimana siswa kelas IV berjumlah 20 siswa, dan V berjumlah 21 siswa, dan siswa kelas VI berjumlah 26 siswa. Jumlah populasinya adalah seluruh siswa kelas tinggi SDN 261 Tarasu Kecamatan Kajuara Kabupaten Bone. Teknik pengambilan sampel pada penelitian ini menggunakan teknik Nonprobability yaitu sampel jenuh. Pengumpulan data melalui angket dan dokumentasi. Teknik analisis data yaitu analisis statistik deskriptif dengan analisis statistik inferensial. Berdasarkan hasil analisis statistik deskriptif diproleh modalitas belajar siswa berada pada kategori baik dengan analisis rata-rata 86,77 dan persentase 72,31%. Prestasi belajar berada pada kategori baik dengan analisis rata-rata 82,62 dan persentase 68,85%. Kemudian berdasarkan statistik inferensial menunjukkan nilai thitung (4,9124) lebih besar (>) nilai ttabel (1,66864) pada taraf signifikansi 5%. Dengan demikia H0 ditolak dan H1 diterima. Dari hasil penelitian diperoleh kesimpulan bahwa ada hubungan yang signifikan antara modalitas belajar dengan prestasi belajar siswa kelas Tinggi SDN 261 Tarasu Kecamatan Kajuara Kabupaten Bone, tetapi modalitas belajar tidak selalu berpengaruh pada prestasi belajar siswa.